Development of Monopoly Mitigation Game (Momi) to Improve Critical Thinking Skills of Early Childhood - Adinda Putri Kartikasari; Mallevi Agustin Ningrum; Kartika Rinakit Adhe; Dhian Gowinda Luh Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research aims to develop and test the effectiveness of the Monopoly Mitigation Game (MOMI) in enhancing critical thinking skills of children aged 5–6 years in the context of earthquake disaster mitigation. The study adopts a research and development design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research was conducted with 21 children from TK ABA 27 Sedayulawas in Lamongan, East Java. The instruments included observation sheets and validation questionnaires. Results showed that the material expert validation scored 87.5% and media expert validation scored 85%, both categorized as